Penentuan Rute Optimal dan Alokasi Kendaraan dalam Pendistribusian Beras di Provinsi Kalimantan Tengah - Olyvia Novawanda; Clifton Suharjono; Leonardy Sentosa (Politeknik ATI Padang, 2023)
Central Kalimantan is one of the most populous provinces in Indonesia where rice has the greatest impact on the calculation of the poverty line. As of August 2022, 0.44 percent of the inflation in Palangkaraya is attributable to rice, which can contribute to an increase in the MPP rate. Margin perdagangan dan pengangkutan (MPP) is a percentage that indicates the increase in rice prices from producers to final consumers, taking into account transportation costs. The objective of this paper is to determine the optimal route and allocation of each vehicle fleet serving each depot, given several constraints using an open-source spreadsheet solver. Vehicle Routing Problem (VRP) is one of the most frequently encountered optimization problems in logistics. In this instance, we optimize the paddy distribution fleet in Central Kalimantan using the VRP method. The results of the data processing led to the choice of the best route that could adhere to all the limitations, demonstrating that the VRP spreadsheet solver could be used for the case in this study. Based on the computations of 13 vehicles, hereinafter referred to as vehicle (V) which serves 100 Customers, it is obtained that V1 will serve 4 Customers, V2 will serve 5 Customers, V3 will serve 26 Customers, V4 will serve 5 Customers, V5 will serve 5 Customers, V6 will serve 6 Customers, V7 serves 3 Customers, V8 serves 4 Customers, V9 serves 14 Customers, V10 serves 5 Customers, V11 serves 3 Customers, V12 serves 11 Customers, and V13 serves 9 Customers.